A new species of Neocerambyx Thomson, 1860 (Coleoptera, Cerambycidae) - Zhu, Li; Yafei, Lu; Li, Chen (Zootaxa, 2020)
A new species of Neocerambyx Thomson, 1860 is described, N. guangxiensis sp. nov., from Guangxi, China. The description and photographs of adult habitus and male genitalia of this new species are provided.